The Impact of Smoking, Drinking and Weight on Coronavirus Disease-19 Symptoms in Korean Airline Crew - Yeo-Won Jeong; Jung-Ha Kim (Hanggong uju uihakoeji, 2025)
Purpose: This study aimed to investigate the differences in Coronavirus disease-2019 (COVID-19) symptoms according to weight among cockpit and cabin crews in Korea. Methods: This study was designed as a cross-sectional survey, comprising 180 cockpit and cabin crew members. Results: Out of 180 participants, 22 participants had no symptoms at the onset. Among the 158 participants who experienced symptoms, the most common ones were fatigue (79.7%), cough (63.9%), and myalgia (63.3%). Participants who did not currently smoke and drank less than once a month reported more symptoms of COVID-19. The number of COVID-19 symptoms was significantly higher in participants with normal weight compared to those who were overweight/obese (P= 0.004). The time taken to return to flight duties after completing COVID-19 treatment was significantly longer for participants with normal weight compared to those who were overweight/obese (P=0.041). Conclusion: Airlines should prioritize fatigue management in crew members recovering from COVID-19. Additionally, smoking and weight have an impact on the severity of COVID-19 in young people; therefore, continuous management is necessary, even if the number of reported symptoms is small.